2022
DOI: 10.1155/2022/8648584
|View full text |Cite
|
Sign up to set email alerts
|

Differences and Correlations of Anxiety, Sleep Quality, and Pressure-Pain Threshold between Patients with Chronic Low Back Pain and Asymptomatic People

Abstract: Background. Chronic low back pain (CLBP) is a clinically common and expensive disease. Patients frequently take sick leaves because of pain and dysfunction, and their unpleasant life and work experiences cause psychological depression and anxiety and affect their quality of life. Sleep disturbance is a common problem among patients with low back pain (LBP) with more than 50% complaining about poor sleep quality. This study aimed to explore the correlations between anxiety, sleep quality, and pressure-pain thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Numerous studies have indicated that patients who experienced chronic pain had significantly lower PPTs compared with healthy controls [ 46 48 ]. In addition, the scores of anxiety and depression scales were significantly correlated with PPT [ 49 51 ]. Although all patients in this study did not take anxiety-depression psychotropic drugs, we could not determine whether the patient's anxiety and depression were present before being diagnosed with CPID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated that patients who experienced chronic pain had significantly lower PPTs compared with healthy controls [ 46 48 ]. In addition, the scores of anxiety and depression scales were significantly correlated with PPT [ 49 51 ]. Although all patients in this study did not take anxiety-depression psychotropic drugs, we could not determine whether the patient's anxiety and depression were present before being diagnosed with CPID.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with group B, the group A had signifcantly higher SAS scores (median 49 (IQR, [45][46][47][48][49][50][51][52][53][54] 3).…”
Section: Te Emotion and Pain Scores In The Two Groupsmentioning
confidence: 92%
“…LBP's etiology is multifactorial and classified according to the mechanism of injury, etiologic diversity, evolutionary time, and degree of radicular involvement (Schitter et al, 2022). These problems can be associated with various types of factors such as age, gender, decreased flexibility and muscle mobility, obesity, competitive Xu et al, 2022). Based on the Riskesdas (Basic Health Research) (2018) results, the prevalence of musculoskeletal disorders in Indonesia that health workers have diagnosed is 11.9%, while based on diagnosis or symptoms is 24.7%.…”
Section: Introductionmentioning
confidence: 99%